PENGARUH PENGETAHUAN, SIKAP DAN KEPERCAYAAN MAHASISWA TERHADAP PRODUK YANG BERLABEL HALAL (STUDI KASUS MAKANAN DAN MINUMAN)N MINUMAN) - Firmansyah Al-Haq; Nurizal Ismail; Sholahuddin Al-Ayubi (I-Economics: A Research Journal on Islamic Economics)
The study aims to analyse the influence of students knowledge, attitudes, and beliefs on products labelled halal, focusing on food and beverages. This study used quantitative methods with a cross-sectional design. Primary data were obtained through the distribution of questionnaires to respondents. The research population focused on in this study is all students who are still active and are not limited by age, religion, ethnicity, or gender. The sampling technique uses non-probability sampling with a purposive sampling approach. The sample size is determined to be at least 100 respondents. The results showed that students knowledge and trust had a positive and significant influence on their acceptance of halal products. However, attitude variables did not show significant influence in this context. This can be interpreted as an indication that, although students have knowledge and trust in halal products, students' attitudes do not significantly influence their preference for these products. The implications of these findings could provide guidance for manufacturers and marketers to better understand the factors influencing consumer preferences towards halal products, focusing on increasing knowledge and trustworthiness.